2009
DOI: 10.1021/om800952t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of Ruthenium Azido Complexes Containing a Hydridotris(pyrazolyl)borate Ligand and Dimerization of Terminal Alkynes in Organic and Aqueous Media

Abstract: Facile ligand substitution is observed when the ruthenium azido complex (PPh 3 )[Ru]-N 3 (1; [Ru] ) Tp(PPh 3 )Ru) is treated with CH 3 CN, yielding the nitrile-substituted ruthenium azido complex (CH 3 CN)[Ru]-N 3 (2). Alkylation, [3 + 2] cycloaddition, and catalytic reactions of complex 2 have been investigated. In the case of [3 + 2] cycloaddition reactions, the metal-bound heterocyclic complexes (CH 3 CN)[Ru]-N 3 C 2 (CO 2 Me) 2 (3a), (CH 3 CN)[Ru]-N 3 C 2 HCO 2 Me (5), and (CH 3 CN)[Ru]-N 3 C 2 HCN (6) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 98 publications
3
25
0
Order By: Relevance
“…Recently, many reports have been generally successfully prepared alkyl vinylidene -linkage to ruthenium core using the special coordinating ligand for example terminal alkyne [1][2][3][4][5] or some vinyl aromatic [6][7]. It is confirmed that alkyne fragments around the metal core do not only functions as protecting ligands promoting the stability of the nanoparticles but also enhances some optical and fluorescence characteristic via the pi-bond interaction between methylene and metal core [8].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Recently, many reports have been generally successfully prepared alkyl vinylidene -linkage to ruthenium core using the special coordinating ligand for example terminal alkyne [1][2][3][4][5] or some vinyl aromatic [6][7]. It is confirmed that alkyne fragments around the metal core do not only functions as protecting ligands promoting the stability of the nanoparticles but also enhances some optical and fluorescence characteristic via the pi-bond interaction between methylene and metal core [8].…”
Section: Introductionmentioning
confidence: 93%
“…Octyne-ruthenium was deposited on CPNs by mixing RuCl 3 , NaBH 4 , and CNPs at the ratio of 3:3:10 in pure water. Briefly describe, 10 mg of CNPs was mixed with 1 mg RuCl 3 in 10 mL of water and stir over night.…”
Section: Synthesis Of Alkyne-ruthenium On Carbon Nanoparticlesmentioning
confidence: 99%
“…Catalytic transformations of organic alkynes mediated by ruthenium complexes are well known, and confirmation for the intermediacy of ruthenium(II) acetylide and vinylidene complexes has been provided (Bruneau & Dixneuf, 1999;Cheng et al, 2009;Naota et al, 1998;Trost et al, 2001). Therefore, ruthenium was a logical choice in our search for a new catalyst of click reaction (Chen et al, 2009). Organic azides are synthetically useful reagents.…”
Section: S1 Commentmentioning
confidence: 99%
“…For catalytic transformations of organic alkynes mediated by ruthenium complexes, see: Naota et al (1998); Bruneau & Dixneuf (1999); Trost et al (2001); Chen et al (2009); Cheng et al (2009). For the synthesis of triazoles, see: Padwa (1976).…”
Section: Related Literaturementioning
confidence: 99%
“…On the other hand, we have reported the first example that dimerization of alkynes with the ruthenium azido complex instead of ruthenium chloride complex to give (E)-enynes carried out in organic and aqueous media [15]. Therefore, ruthenium azido complex was a logical choice in our search for a new catalyst of click reaction.…”
Section: Selection Of Catalystsmentioning
confidence: 99%